Associated Factors with Recurrent Wheezing in Infants: Is There Difference Between the Sexes? - Mallol-Villablanca, E (Elsevier Editora Ltda, 2021)
Objective: Identify associated factors for recurrent wheezing (RW) in male and female infants. Methods: Cross-sectional multicentric study using the standardized questionnaire from the Estudio Internacional sobre Sibilancias en Lactantes (EISL). The questionnaire was applied to parents of 9345 infants aged 12–15 months at the time of immunization/routine visits. Results: One thousand two hundred and sixty-one (13.5%) males and nine hundred sixty-three (10.3%) females have had RW (≥3 episodes), respectively (p10 colds episodes (OR = 3.46; IC 95% 2.35–5.07), air pollution (OR = 1.33; IC 95% 1.12–1.59), molds at home (OR = 1.23; IC 95% 1.03–1.47), Afro-descendants (OR = 1.42; IC 95% 1.20–1.69), bronchopneumonia (OR = 1.41; IC; 1.11–1.78), severe episodes of wheezing in the first year (OR = 1.56; IC 95% 1.29–1.89), treatment with bronchodilators (OR = 1.60; IC 95% 1.22–2,1) and treatment with oral corticosteroids (OR = 1,23; IC 95% 0.99–1,52). Associated factors for RW for females were passive smoking (OR = 1.24; IC 95% 1.01−1,51), parents diagnosed with asthma (OR = 1.32; IC 95% 1,08−1,62), parents with allergic rhinitis (OR = 1.26; IC 95% 1.04–1.53), daycare attendance (OR = 1.48; IC 95% 1.17−1,88), colds in the first 6 months of life (OR = 2.19; IC 95% 1.69–2.82), personal diagnosis of asthma (OR = 1.84; IC 95% 1.39–2.44), emergency room visits (OR = 1.78; IC 95% 1.44–2.21), nighttime symptoms (OR = 2.89; IC 95% 2.34–3.53) and updated immunization (OR = 0.62; IC 95% 0.41−0.96). Conclusion: There are differences in associated factors for RW between genders. Identification of these differences could be useful to the approach and management of RW between boys and girls. © 2021 Sociedade Brasileira de Pediatria